2021
DOI: 10.3390/mi12111277
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Power RRAM Memory Block for Embedded, Multi-Level Weight and Bias Storage in Artificial Neural Networks

Abstract: Pattern recognition as a computing task is very well suited for machine learning algorithms utilizing artificial neural networks (ANNs). Computing systems using ANNs usually require some sort of data storage to store the weights and bias values for the processing elements of the individual neurons. This paper introduces a memory block using resistive memory cells (RRAM) to realize this weight and bias storage in an embedded and distributed way while also offering programming and multi-level ability. By impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The high-density integration on the chip allows for the ReRAM cells to be closely attached to digital computation units, which decreases energy consumption by avoiding long data paths on the chip. The use of ReRAM technology yielded a 95% reduction in energy consumption for the classification of bio-signals for atrial fibrillation compared to a traditional approach (Pechmann et al, 2021 ). Therefore, ReRAM technology is a promising candidate for realization of personalized gait neuroprostheses relying on artificial neural networks in digital (e.g., as ReRAM storage for weights) and analog in-memory processing (e.g., as an in-memory processing element itself).…”
Section: Interface With the Embedded Computer Architecturementioning
confidence: 99%
“…The high-density integration on the chip allows for the ReRAM cells to be closely attached to digital computation units, which decreases energy consumption by avoiding long data paths on the chip. The use of ReRAM technology yielded a 95% reduction in energy consumption for the classification of bio-signals for atrial fibrillation compared to a traditional approach (Pechmann et al, 2021 ). Therefore, ReRAM technology is a promising candidate for realization of personalized gait neuroprostheses relying on artificial neural networks in digital (e.g., as ReRAM storage for weights) and analog in-memory processing (e.g., as an in-memory processing element itself).…”
Section: Interface With the Embedded Computer Architecturementioning
confidence: 99%
“…However, the use of more states is also possible. The design of this RRAM memory block has been optimized specifically for use in low-power accelerators for NNs [29].…”
Section: Non-volatile On-chip Rrammentioning
confidence: 99%
“…The operation results in a two-element output current vector represented by I 1 and I 2 . Recently, the research community has intensively studied and optimized the performance of the RRAM technology within in-memory MAC-based systems/circuits, specially in simulation environments for early-stage design exploration [13], [14], [15], [16]. Among others, Mehonic et al [17] reported hand-written digit recognition with up to 97% accuracy ratio using an RRAM-based ANN.…”
mentioning
confidence: 99%